2020
DOI: 10.1177/1945892420932487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exposure to Cats and Dogs on the Risk of Asthma and Allergic Rhinitis: A Systematic Review and Meta-analysis

Abstract: Background Controversies persist regarding whether exposure to cat or dog increases the risk of asthma and allergic rhinitis. Objective This meta-analysis aimed to assess the associations between exposure to cats or dogs and the development of asthma and allergic rhinitis. Methods A systematic review was performed to identify case-control and cohort studies before May 2019, evaluating the association between exposure to cats and dogs and the risk of asthma and rhinitis. The risk of bias was assessed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 118 publications
1
14
0
Order By: Relevance
“…The picture from systematic reviews and meta-analyses of published aggregate cohort data examining associations of pet ownership with asthma is less clear; such studies have reported null or weak and inconsistent associations, with substantial betweenstudy heterogeneity. 29,66,67 The current meta-analysis adds to the current body of knowledge by demonstrating a lack of association regardless of number of pets owned and with lung function, but potentially a small protective effect in the absence of sensitization and harmful effect in the presence of sensitization.…”
Section: Comparison With the Literature And Interpretation Of Resultsmentioning
confidence: 77%
“…The picture from systematic reviews and meta-analyses of published aggregate cohort data examining associations of pet ownership with asthma is less clear; such studies have reported null or weak and inconsistent associations, with substantial betweenstudy heterogeneity. 29,66,67 The current meta-analysis adds to the current body of knowledge by demonstrating a lack of association regardless of number of pets owned and with lung function, but potentially a small protective effect in the absence of sensitization and harmful effect in the presence of sensitization.…”
Section: Comparison With the Literature And Interpretation Of Resultsmentioning
confidence: 77%
“…There is the possibility of reverse causality, including the possibility that there may be misdiagnosis of bronchiolitis that was actually asthma, and equally possible that later asthma is also misdiagnosed. (7) The study by Lin H-W and Lin S-C 34 has also shown that infants with bronchiolitis are at increased risk for developing asthma. Excluding this study for statistical reason would not change the overall conclusions but would change the pooled risk estimates.…”
Section: Open Accessmentioning
confidence: 99%
“…Exposure to smoke, 4 male gender, atopic dermatitis, family history of asthma, history of wheezing and serum IgE level ≥60 kU/L or having specific IgE are found to be positively associated with developing asthma. 5 Breastfeeding 6 and exposure to cats and dogs 7 seem to play protective roles in the development of asthma. However, the associations between high adherence of the Mediterranean diet during pregnancy and childhood 8 and swing attendance during childhood 9 with asthma are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is interesting that sensitization to Fel d 1, but not to Can f 1, was positively associated with PFAS development. Some studies have shown that dog ownership, but not cat ownership, is negatively associated with the occurrence of allergic comorbidities [25,26]. This suggests that the sensitization of dog-derived allergens could have a preventive effect on subsequent PFAS development, although further detailed studies are required.…”
Section: Discussionmentioning
confidence: 99%